79 ADIPOSE TISSUE MACROPHAGES EXPRESS HIGH LEVELS OF PLASMINOGEN ACTIVATOR INHIBITOR 1 IN HUMANS AND ARE HIGHLY RESPONSIVE TO INCREASED FREE FATTY ACIDS. (1st March 2006) - Lee, D.-E.; Koppaka, S.; Kishore, P.; Li, W.; Tonelli, J.; Scherer, P. E.; Goodman, E.; Hawkins, M.
Abstract : Plasminogen activator inhibitor 1 (PAI-1) levels are increased in obesity and the metabolic syndrome and heighten the risk of atherothrombotic disease. Since obesity is characterized by adipose tissue macrophage infiltration (JCI 112:1796 and 1821, 2003), we proposed that adipose macrophages might be an important source of circulating PAI-1. We therefore biopsied subcutaneous abdominal (SAT) and omental (OAT) adipose tissue in six nondiabetic elective surgery patients (4 F/2 M, age 33 ± 3 years, BMI 31.9 ± 1.5 kg/m 2 ). Following collagenase digestion and adipocyte filtration, macrophages were separated from other stromal cells by CD14-coated Dynabeads (Å80% recovery). Gene expression was quantified by real-time rt-PCR using plasmid standard curves. PAI-1 gene expression was Å2-fold higher in SAT vs OAT (whole fat) and 4-fold higher in macrophages and stromal cells than in adipocytes. We previously showed that increasing free fatty acids (FFA) up to levels seen in obesity stimulated PAI-1 gene expression in adipose tissue. Therefore, we hypothesized that FFA have stimulatory effects on PAI-1 expression in adipose tissue macrophages. Subcutaneous abdominal fat was biopsied in 17 obese nondiabetic subjects (5 F/12 M, age 45 ± 4 years, BMI 30 ± 1 kg/m 2 ) after 5-hour euglycemic (5mM) insulin (40 mU/m 2 .min) clamp studies, with infusion of saline (Sal) or Liposyn 20% (Lip). Increasing FFA to Å800 mM for 5 hours induced 5-fold increases in whole adipose tissue PAI-1 gene expression ( p < .01 vs Sal) but no change in macrophage (CD68 and CD14) gene expression. After only 2 hours of increased FFA, PAI-1 gene expression increased by 2.6-fold in whole fat and 1.8-fold in adipose tissue macrophages while there was no change in circulating blood monocytes. Conclusions: In human fat, macrophages express high levels of PAI-1. Elevated FFA rapidly increase PAI-1 expression in fat tissue and in resident macrophages. Since circulating monocytes did not respond to FFA, enhanced stimulation of PAI-1 expression in adipose tissue macrophages may be influenced by local adipocyte secretory products.